Antifospholipid Syndrome with Autoimun Hemolitic Anemia - Muhammad Huki Zukhrufan; Irza Wahid (Berkala Kedokteran, 2020)
Abstract: Antiphospholipid syndrome is a part of systemic autoimmune disease (nonspecific organ), characterized by vascular thrombosis (arterial or venous) with a high antibody titter against a plasma protein that binds to phospholipid anions (antiphospholipid-aPL antibodies). Autoimmune haemolytic anaemia (AIHA) is rare in patients with antiphospholipid antibody syndrome. A sixteen years old female patient has been reported with the main complaint of swelling in the right leg. The patient also complained of increased fatigue. On physical examination found anaemic conjunctiva, swelling in the right limb with a diameter of the right leg greater than the left leg. Homan’s sign positive on the right leg. This patient belongs to the high probability criteria of DVT. Doppler Ultrasonography (USG) examination suggests thrombus in the iliac vein, femoral vein, and right leg popliteal vein, and thrombus in the left leg popliteal vein. In the antibody anticardiolipin (ACA) IgG examination an increase was found. The comb test was positive, and haemolytic anaemia antibody screening was the warm type. Heparinisation and immunosuppressant administration were performed in patients. The incidence of antiphospholipid syndrome with AIHA cannot be ascertained whether there is a direct relationship. Keywords: antiphospholipid syndrome, DVT, AIHA